Manpower Efficiency on Soybean Farming System at Peaty Acid Sulphate Land - Umar, Sudirman; Saleh, Muhammad (Jurnal Teknologi Pertanian, 2012)
Physical manpower is the most power that used for fulfill rice and upland farming from land preparation to post harvest. Research was conducted at Lamunti village, Kapuas regency, Central Kalimantan in May to August 2009. The object of research was to evaluate the energy consumption in production processes with energy output that produced by soybean production. Data were collected from 30 soybean farmers by questinnaire method, then compared with land preparation to post harvest activity Energy and cost analysis was calculated based on energy consumption of each activity, physical energy (manpower), production facilities and energy output. The result showed that soybean farming on peaty acid sulfate land used work hour as 652.20 J/ha or equivalent with of physical energy as much as 182914.26 kkal/ha of total energy needs. Total energy that needed for manage soybeans farming for one ha was 1446076.00 kkal. Cost of manpower was 53.38% of total production costs. Whereas energy output and the output cost were 5292000 kkal/ha and Rp. 10290000.00 or increased as 67.89%. Production efficiency was determined by the level of production facilities. In the production process, higher the chemical energy input, lower the value of production efficiency. Keywords: energy, tidal land, soybean